2011
DOI: 10.1002/ijch.201100042
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbiturils as Versatile Receptors for Redox Active Substrates

Abstract: Research on the chemistry of cucurbit[n]uril (CBn) hosts has picked up and maintained an impressive pace in the last decade, primarily due to the isolation of hosts with relatively larger cavity sizes, such as CB7 and CB8. This review article summarizes our involvement in this research effort, with particular emphasis on the binding of redox active guests by the CB7 and CB8 hosts. The binding of 4,4′‐bipyridinium (viologen) derivatives was the starting point of our CB research. While methylviologen is encapsul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 41 publications
(47 reference statements)
1
51
0
Order By: Relevance
“…1,2 This affinity pair has been exploited in many applications including enzyme-linked immunosorbent assays, protein and nucleic acid detection and purification, and immobilization of biomolecules on surfaces. [30][31][32][33][34][35][36][37][38][39] Isaacs, Kim, and others reported that this host family forms exceptionally stable host-guest complexes with specific guest molecules. Also, the interaction between avidin and biotin can be undesirably affected by bio-systems, thus limiting their biological applications.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 This affinity pair has been exploited in many applications including enzyme-linked immunosorbent assays, protein and nucleic acid detection and purification, and immobilization of biomolecules on surfaces. [30][31][32][33][34][35][36][37][38][39] Isaacs, Kim, and others reported that this host family forms exceptionally stable host-guest complexes with specific guest molecules. Also, the interaction between avidin and biotin can be undesirably affected by bio-systems, thus limiting their biological applications.…”
Section: Introductionmentioning
confidence: 99%
“…[10] The observed reduction in K a for CB [7]·4 in NaO 2 CCD 3 (50 mm) is fully consistent with the known ability of Na + ions to bind at the C=O portals of CB[n], and thereby reduce the observed values of K a by competition. [11] In the intervening years, some researchers have augmented known scaffolds, [12] explored new guest scaffolds (such as bicyclo-[2.2.2]octane), [13,14] whereas others have demonstrated the importance of the release of high-energy waters during the formation of CB [7]·guest complexes. [15] Despite this wide body of work, the tightest-binding CB [7]·guest complex known to date is the complex between CB [7] and adamantane derivative 5 (CB [7]·5: K a = 5 10 15 m À1 in pure water; measured herein as K a = 2.4 10 13 m À1 in D 2 O buffered with NaO 2 CCD 3 (50 mm) at pH 4.74; see below), which was reported in 2011.…”
mentioning
confidence: 99%
“…Mechanistic aspects of proline-catalysed aldol reactions have been extensively studied via computational/experimental combined approaches. [1b] We rather focused our interest on the study of the thermodynamics of the interaction between the cucurbituril unit [33] and the catalytic active species, and its influence on catalyst recycling. We selected the first system, Figure 2.…”
Section: Computational Resultsmentioning
confidence: 99%